Synthesis of New Carbohydrate Derivatives Via 1,3-Dipolarcycloaddition Reaction - Sharba, A Hussain K; Askar, Firyal W; Al-Fattahi, Yousif A (Al-Nahrain Journal of Science, 2011)
This work describes the synthesis of a new fructofuranosyl derivatives comprising 1,2,3-triazole, 1,2,3-triazoline or tetrazole rings via 1,3-dipolar cycloaddition reaction. To obtain these derivatives, 1,3,4,6-tetra-O-benzoyl-β-D-fructofuranose (1) with free hydroxyl group at position-2 was prepared as the starting material. Reaction of compound (1) with 45% HBr solution in glacial acetic acid gave compound (2). The bromide (2) was then made to react with some nucleophiles (NaN3 and KCN) to give 1,3,4,6-tetra-O-benzoyl-β-D-fructofuranosyl azide (3) and 1,3,4,6-tetra-O-benzoyl-β-D-fructofuranosyl cyanide (4). Treatment of compound (3) with cinnamic acid, cinnamaldehyde, acrylic acid, acrylonitrile, acrylamide and maleic anhydride, gave the triazoline derivatives (5-10). Cycloaddition reaction was also carried out with propargyl chloride, propargyl alcohol and 1-hexyn-3-ol using (ph3P)3CuI as a catalyst to give the triazole derivatives (12-14). Reaction of the cyanosugar (4) with arylsulfonyl azides gave the tetrazole derivatives (16-18). Antibacterial and antifungal activities of some novel synthesized compounds were studied and compared with that of two well known antibiotics (Ampicillin and Gentamycin).